Gross anatomy of the nasal cavity in sheep (Ovis aries) - GANGANAIK, S; JAIN, R K; KUMAR, PAWAN (The Indian Journal of Animal Sciences, 2014)
Six sheep heads of either sex and approximately 1-1Â½ years-old of local mixed breed were examined. The nasal cavity in sheep was completely divided into 2 compartments by a median nasal septum. Tne dorsal nasal turbinate was thelongest and extended from the ceribriform plate of ethmoid bone to the level of second transverse ruga of hard palate. It continued rostrally as straight fold and contained a sinus. The ventral nasal turbinate Was fusiform in shape and extended from the second molar tooth to the third transverse ruga of hard palate. The middle nasal turbinate was triangular in outline and extended upto the first molar tooth. The ethmoturbinate had 5 endoturbinates and 6 ectoturbinates.